The Relationship between Corporate Social Responsibility of Hotels and Brand Equity in Ho Chi Minh City, the Mediating Role Of Customers - Thanh, Phung Tuan; Hac, Le Dinh; Dat, Tran Van (Advances in Social Sciences Research Journal, 2024)
The impact of Corporate Social Responsibility on Brand Equity has been clearly demonstrated in both theory and practice; however, there is still no consensus on which factors influence this impact. This study aims to construct a model focusing on understanding the impact of CSR on Brand Equity through Customer Commitment. A survey was conducted with 500 customers at 4-star and 5-star hotels in Ho Chi Minh City, using the PLS-SEM analysis tool. The research results indicate a direct impact between Corporate Social Responsibility and Brand Equity, while also demonstrating the positive mediating relationship of Customer Commitment.